2015
DOI: 10.3892/or.2015.3937
|View full text |Cite
|
Sign up to set email alerts
|

Urinary microRNA-30a-5p is a potential biomarker for ovarian serous adenocarcinoma

Abstract: MicroRNAs (miRNAs) can serve as biomarkers in human cancer. To determine the clinical value of urinary miRNAs for ovarian serous adenocarcinoma, we collected urine samples from 39 ovarian serous adenocarcinoma patients, 26 patients with benign gynecological disease and 30 healthy controls. The miRNA microarray data showed that only miR-30a-5p was upregulated and 37 miRNAs were downregulated in the urine samples of ovarian serous adenocarcinoma patients, when compared to healthy controls, which was confirmed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 30 publications
1
133
0
2
Order By: Relevance
“…23,24 Only a few studies reported that miR-30a existed in exosomes, and the levels of miR-30a derived from exosomes in urine, serum or plasma, and saliva could be used as non-invasive biomarkers for screening and diagnosing a certain type of cancer. [25][26][27] Our results indicate that hundreds of particular miRNAs were upregulated in exosomes from cancer cells compared with that from normal cells. Of these differentially expressed miRNAs, microRNA-100 (miR-100) and microRNA-148a (miR-148a) were picked out to validate by qRT-PCR; finally, the trend was similar to that of miRNA sequencing.…”
Section: Discussionmentioning
confidence: 67%
“…23,24 Only a few studies reported that miR-30a existed in exosomes, and the levels of miR-30a derived from exosomes in urine, serum or plasma, and saliva could be used as non-invasive biomarkers for screening and diagnosing a certain type of cancer. [25][26][27] Our results indicate that hundreds of particular miRNAs were upregulated in exosomes from cancer cells compared with that from normal cells. Of these differentially expressed miRNAs, microRNA-100 (miR-100) and microRNA-148a (miR-148a) were picked out to validate by qRT-PCR; finally, the trend was similar to that of miRNA sequencing.…”
Section: Discussionmentioning
confidence: 67%
“…The same pattern was not observed in other solid tumors such as gastric cancer and colon-rectal carcinoma patients suggesting that the upregulation of urinary miR-30a-5p may be specific for ovarian serous adenocarcinoma. 53 Despite these interesting and promising findings, further studies need to be carried out in larger scales to better assess the significance and the role of urinary miRNAs in OC patients.…”
Section: Urinary Mirnasmentioning
confidence: 99%
“…Urinary excretion of miR-30a-5p is found in serous ovarian cancer but not in other cancer types. After primary debulking surgery, less expression of miR-30a-5p is found in the urine (56). While Zhou et al (56) did not examine the expression of miR-30a-5p after recurrence of ovarian cancer, this microRNA may serve as a useful biomarker for determination of disease.…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%
“…After primary debulking surgery, less expression of miR-30a-5p is found in the urine (56). While Zhou et al (56) did not examine the expression of miR-30a-5p after recurrence of ovarian cancer, this microRNA may serve as a useful biomarker for determination of disease. Langhe et al (57) used a discovery set of five malignant high-grade serous and five benign serous cystadenomas to examine the expression of microRNA levels in blood.…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%